PENERAPAN E-FILING, E-BILLING DAN PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA MEDAN POLONIA - Syamsul Bahri Arifin; Indra Syafii (Universitas Medan Area, 2019)
This study aims to determine and analyze the effect of the application of e-filling, e-billing and tax audit on individual taxpayer compliance in Medan Polonia KPP. The sample used in this study as 100 Individual taxpayers in the Polonia Medan Primary Tax Office area. This study uses a quantitative analysis method that explains the state of the variables studied using statistical data. All indicators from this study should pass the validity test and data reality, the classical assumption test and final hypothesis test. The results of this study indicate that there are insignificant effects from free variables in the form of the application of e-filing, application of e-billing and tax audits of individual taxpayer compliance at Medan Polonia Tax Office. The ability of the three independent variables in explaining the dependent variable is very small, which is only 3% while the remaining 97% is explained by other variables were not included in this research model.